Myosin Va but Not nNOSα is Significantly Reduced in Jejunal Musculomotor Nerve Terminals in Diabetes Mellitus - Chaudhury, Arun; De Miranda-Neto, Marcilio Hubner; Pereira, Renata Virginia Fernandes; Zanoni, Jacqueline Nelisis (Frontiers in Medicine, 2014)
Nitric oxide (NO) mediated slow inhibitory junction potential and mechanical relaxation after electrical field stimulation (EFS) is impaired in diabetes mellitus. Externally added NO donor restore nitrergic function, indicating that this reduction result from diminution of NO synthesis within the pre-junctional nerve terminals. The present study aimed to investigate two specific aims that may potentially provide pathophysiological insights into diabetic nitrergic neuropathy. Specifically, alteration in nNOSα contents within jejunal nerve terminals and a local subcortical transporter myosin Va was tested 16 weeks after induction of diabetes by low dose streptozotocin (STZ) in male Wistar rats. The results show that diabetic rats, in contrast to vehicle treated animals, have: (a) nearly absent myosin Va expression in nerve terminals of axons innervating smooth muscles and (b) significant decrease of myosin Va in neuronal soma of myenteric plexus. In contrast, nNOSα staining in diabetic jejunum neuromuscular strips showed near intact expression in neuronal cell bodies. The space occupancy of nitrergic nerve fibers was comparable between groups. Normal concentration of nNOSα was visualized within a majority of nitrergic terminals in diabetes, suggesting intact axonal transport of nNOSα to distant nerve terminals. These results reveal the dissociation between presences of nNOSα in the nerve terminals but deficiency of its transporter myosin Va in the jejunum of diabetic rats. This significant observation of reduced motor protein myosin Va within jejunal nerve terminals may potentially explain impairment of pre-junctional NO synthesis during EFS of diabetic gut neuromuscular strips despite presence of the nitrergic synthetic enzyme nNOSα.